Inter-observer reliability of a real-time observation tool in handball - Gonzalez-Garcia, I.; Casais Martinez, L.; Viano Santasmarinas, J.; Gomez Ruano, M. A. (International Journal of Kinesiology & Sports Science, 2016)
The analysis of the competition in real time is currently one of the most important aspects to develop the sport. The purpose of the analysis should be creating valid and reliable knowledge for coaches to make the best decisions in a situation of competition. Objectives: This study was to determine the inter-observer reliability of the real-time observation tool for handball. Methods: Two groups of two observers each one were required to analyze the men's handball final of the London 2012 Olympic Games (average age: 23.72 ± 2.16 years; experience as handball players: 14.69 ± 1.92 years; experience as coaches: 4.64 ± 4.04 years). The process of training of the observers lasted 22 days, accounting twelve hours of work distributed in 12 training sessions. Results: The reliability showed a very good agreement between the independent observers (Kappa values were 0.96 and 0.90) in the registered events of both teams, and a very good agreement (Kappa values were 0.85 and 0.94) of the registered actions of the goalkeepers. The high coefficient of intra-class correlation with a value of 0.98 and the low value of the standard error with a 0.11 of the actions of the players of both teams showed a high level of inter-observer reliability. Conclusions: These results showed that the tool of observation in handball is reliable for registering the events of a real time match by well-trained observers. With the help of the HandballTAS and using technology, large volumes of real-time data were collected in a simple and easily usable